(untitled) (Research, Society and Development, 2022)
To report the experience of nurses during care management in the face of the COVID-19 pandemic, in the adult intensive care unit. This is an experience report about the challenges of the nurse professional in care management, in an adult intensive care unit, during the COVID-19 pandemic. The contents were organized into two thematic axes: I – Challenges of managing the nursing service during the COVID-19 pandemic. II – Challenges of nursing care during the COVID-19 pandemic. The study was limited to the experience of the professional nurse from May 2020 to May 2021 in the Intensive Care Unit of a philanthropic Hospital, in Rio Branco-Acre. The nurse’s responsibility in care management, during COVID-19 in the Intensive Care Unit, demanded planning, organization and proactivity in actions and quality in leadership in clinical and managerial care. However, although it is a contemporary morbidity, and with many professionals with limited qualifications in the management of the disease, the entire team was active in coping with the disease and the challenges imposed by it.